Edukasi dan Sosialisasi Pengelolaan Sampah Domestik di Desa Ciambar Sukabumi - Septiani, Winnie; Akbari, Annisa Dewi; Aphirta, Sarah; Putri, Khusnul Ramadhan Eka; Ramadhana, Anisa Suci (Abdimas Universal, 2026)
Rubbish has become a national problem in Indonesia, including in Ciambar Village, Sukabumi. Public awareness and participation in Ciambar Village is still lacking. This is due to the lack of public knowledge regarding the basic principles of waste management through 3R (reduce, reuse, and recycle) and the lack of public knowledge about the potential of a circular economy. Therefore, it is necessary to conduct education and socialization of domestic waste management in Ciambar. This PkM aims to improve awareness and ability of the Cianjur village community to manage waste in the form of implementation of waste processing activities to reduce the amount of waste and increase the utility of waste through waste banks. This PkM is a multidisciplinary PKM that aims to Downstream the results of multidisciplinary research that provides acceleration of quality and quantity to realize Village SDGs. In this PKM there are two materials, namely materials on education and socialization regarding the urgency of implementing good waste management and regarding the right ways and methods of waste management. Based on the results of the evaluation of understanding the material, it was found that almost all participants had understood the material provided. Feedback from beneficiaries indicates that this activity provides great benefits and a desire to continue the program.